Nickel Ore Mining Waste as a Promising Source of Magnesium and Silicon for a Smart-Agricultural Management - Crusciol, Carlos A. C.; de Campos, Murilo; Momesso, Letusa; Bossolani, Joao W.; Moretti, Luiz G.; Portugal, Jose R.; de Melo, Carlos V. C. B.; Calonego, Juliano C. (Frontiers in Environmental Science, 2022)
Thermomagnesium (TM), a byproduct of Ni ore mining, can be processed as a clean alternative to conventional fertilizers as a source of magnesium (Mg) and silicon (Si) for agriculture. TM positively impacts soil properties and provides nutrients that are available for uptake by plants; however, information on the effects of TM on plant physiology in cropping systems is limited. This study aimed to evaluate the impact of increasing doses of TM on crop yield; soil chemical attributes; and leaf contents of Mg, Si, reducing sugars, sucrose, and starch in a soybean-maize crop rotation system. The study was performed under rainfed conditions during three consecutive crop seasons in 2018/2019 (soybean), 2019 (maize), and 2019/2020 (soybean). Six TM doses (0, 350, 700, 1050, 1400, 1750 kg ha-1) with four replicates were applied prior to the first season. Responses to the application of TM were observed up to the highest doses (1400 and 1750 kg ha-1), with increases in soil concentrations of Mg and Si, soil pH, leaf pigments, gas exchange parameters, and carbohydrate concentrations but decreases in starch content. The increases in photosynthetic rates and carbohydrate partitioning led to increases in the weight of 100 grains (W100G) and grain yield (GY). W100G increased by 11% in soybean at a TM dose of 1050 kg ha-1 and 23% in maize at a TM dose of 1400 kg ha-1 dose. For both crops, the greatest increases in GY were obtained at a TM dose of 1050 kg ha-1, with increases of 1068 and 3658 kg ha-1 for soybean and maize, respectively, compared with the control. Therefore, TM can be used as an alternative source of Mg and Si to promote sustainable agriculture and reduce Ni ore mining waste.